Etnobotânica Yéba mahsã: glossário das plantas de cultivo tradicional - Barbosa, Jonas Prado (Universidade Federal de São Carlos, 2025)
This study aims to document the terminology of traditional cultivated plants of the Yéba mahsã people through the compilation of a bilingual glossary (Yéba mahsã–Portuguese), with a view to promoting the linguistic and cultural valorization of this Indigenous ethnic group from the Upper Rio Negro region, located in the municipality of São Gabriel da Cachoeira, Amazonas, Brazil. The research is motivated by the sociolinguistic context, characterized by multilingualism and by the process of weakening of the Yéba mahsã language, which has been increasingly pressured by majority languages such as Tukano and Tuyuka. Grounded in studies of Terminology, Ethnobotany, and Language Policies, the research focuses on the relationship between language, culture, traditional knowledge, and spirituality, demonstrating that plant naming is not limited to botanical classification, but rather expresses cosmological, mythological, and ritual conceptions. The methodology adopted is qualitative, ethnographic, and descriptive, and was developed in successive stages: bibliographic review, field data collection with speakers of the language, and the organization of the data into a terminological work. Species cultivated in agricultural plots were selected, and data were collected on their names in Yéba mahsã, their equivalents in Portuguese, as well as their scientific identification and the elaboration of definitions integrating botanical characteristics and food, medicinal, ritual, and symbolic uses. The study concludes that terminological documentation constitutes an important instrument for linguistic preservation, cultural strengthening, and the safeguarding of the traditional knowledge of the Yéba mahsã people.
Ethnobotany of the Yéba mahsã: a glossary of traditionally cultivated plants
Keywords: Terminologia; línguas indígenas; Yéba mahsã; etnobotânica; glossário Yéba Mahsã - Português; Terminology; Indigenous languages; Yéba mahsã; ethnobotany; Yéba mahsã–Portuguese glossary; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; 10. Redução das Desigualdades